Über gewisse Masse - Tschazkaja, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Е. Ш. Чацкая, О некоторых мерах E. Čackaja, Kai kurių matų klausimu